Phonse Ducey's Twine Store, SW view, Keels, NL - Whitney, Erin (2012)
Phonse Ducey's twine store, Keels, NL. Built in 1950s as a home for Felix Penny. Construction was supervised by Reg Chapman and assisted by Felix Penny, Alvin Hobbs and others in the community.